Respon Pemberian Pupuk Anorganik dan Waktu Penyiangan Terhadap Pertumbuhan dan Hasil Tanaman Kacang Hijau (Vigna radiata L.) - Nuki, Riska Pransiska; Musa, Nikmah; Zakaria, Fauzan (Jurnal Lahan Pertanian Tropis (JLPT), 2025)
Mung bean plant is one of the most popular sources of plant-based protein as a daily food ingredient. In Indonesia, mung beans are one of the most important legume commodities after soybeans and peanuts. The objective of this research is to determine the effect of inorganic fertilizer dosage and weeding time, as well as the interaction between inorganic fertilizer and weeding time, on the growth and yield of mung bean plants. This research was conducted in Libungo Village, Suwawa Selatan Subdistrict, Bone Bolango Regency, and observations of destructive variables were carried out at the Agrotechnology Department Laboratory, Faculty of Agriculture, Universitas Negeri Gorontalo. The factorial RBD design was used, consisting of two factors. The first factor was the application of inorganic fertilizer, with two levels (150 kg/ha and 300 kg/ha), and the second factor was weeding time, with three levels (no weeding, weeding at 7 and 14 days after sowing, and weeding at 7, 14, and 21 days after sowing). The results showed that the application of inorganic fertilizer, weeding time, and the interaction between inorganic fertilizer and weeding time did not have a significant effect on all parameters, including leaf area, leaf area index, plant growth rate, flowering percentage, pod number, weight of 100 seeds, and yield per plot.  Keywords: Mung Bean, Inorganic NPK Fertilizer, Weeding Time